The Role of Parents in Supporting Technology Based Learning Models in Early Children - Safitri, Ika; Fatona, Yusliana; Safrila, Bella; Fitrah Andikos, Adi (Journal of Asian Primary Education (JoAPE), 2024)
Education in the 21st century has entered the era of industrial revolution 4.0 so it is required to continue to innovate. Early Childhood Education (PAUD) as one of the basic education institutions, must be prepared to answer the challenges of current developments. In this technological era, educators must create effective digital learning and provide real learning experiences for children. The aim of this research is to determine the role of parents in supporting technology-based learning in early childhood. The method used in this research is literature study by collecting and reviewing library data which is then connected to research to get answers to problems. The results of research on the role of parents in supporting technology-based learning in early childhood are very much needed in realizing the success of technology-based learning programs in early childhood